DEVELOPING FLASHCARDS AND ITS MANUAL BOOK FOR TEACHING VOCABULARY IN GRADE SIX - Suprianti, G.A.P; Mahayanti, N. W. S.; Kusuma, I. P. I. (International Journal of Language and Literature, 2018)
This research aimed at (1) developingflashcards and its manual book for teaching English in grade sixin Buleleng regency, and (2) finding out the quality of developed flashcards and its manual book. The subject of this research werethree English teachers and eighty students in grade six fromthree schools, that is,the students at SDN 4 Banyuasri, SDN 3 Jagaraga and SDN 9 Banjar. This research was R & D (research and development) which followed threesteps based on ADDIE model, namely Analyze, Design and Development. Since only three steps were undergone in this research, the developed media were still in the form of prototype. The data of this research were obtained by syllabus analysis, using observation sheet, students’ questionnaire, teachers’ questionnaire, teachers’ interview guide, and expert judgement rubric. The result of the present research are flashcards and its manual book. The flashcards and its manual book were developed based on four topics mentioned in the syllabus, namely fruits, vegetables, foods and beverages. Each topic developed consisted of 10 flashcards. Moreover, for the manual book developed, there were five activities provided. For the quality of the media, it was found that flashcards and its manual book developed were categorized as excellent media. Thus, it is proper to be used as media for teaching English vocabulary in grade six. Keywords: flashcards, manual book, teaching English for young learners